Brain Abscess as a Rare Complication of Primary Extranodal Nasal-type Natural Killer/T-cell Lymphoma - Ohta, Nobuo (Yonago Acta Med, 2020)
We present the case of a 58-year-old Japanese woman with a natural killer T (NK/T)-cell lymphoma complicated by brain abscess. NK/T-cell lymphomas represent a rare type of lymphoma derived from either activated NK cells or, rarely, cytotoxic T cells. They are aggressive Epstein-Barr virus (EBV)-associated lymphomas that involve mainly the nasal cavity. Brain abscess associated with primary extranodal nasal-type NK/T-cell lymphoma is extremely uncommon: to our knowledge, this is the first reported case of this lymphoma with brain abscess as the initial clinical manifestation. Endoscopic surgery was performed for definitive diagnosis under intraoperative navigation system. Chemotherapy followed by radiotherapy was performed and was effective: 72 months later the tumor has not recurred. Recommendations of endoscopic management for diagnosis and treatment of this rare neoplasm are discussed.